Expatriate Adjusment And Job Performance Multinational Company: A Systematic Literatur Review - Rosa Indah Parawansah; Madziatul Churiyah; Arief Noviarakhman Zagladi (Universitas Muhammadiyah Metro, 2025)
By using PRISMA principles, this literature review succeeded in identifying relevant researchoriginating from Scopus indexed articles. This analysis groups themes and shows theinterrelationships of emerging themes using Watase Uake software. The results of thissystematic literature review indicate that expatriates need to pay attention to the new culturein their workplace; they also need organizational and family support; Pre-departure trainingprograms aimed at increasing intelligence, such as language training, can speed expatriateadjustment. Apart from that, good adaptability is very important for expatriates. Apart fromthe things above, an expatriate needs cultural adjustment or adjustment. Efforts by bothparties, namely expatriates and the company concerned, to reduce barriers to cultural andenvironm